Math, asked by vandesh, 1 year ago


x {}^{2}  - 3 \sqrt{3}  + 6 = 0 \: factorisation \: method

Answers

Answered by Panzer786
1
Heya !!




X² - 3√3X + 6 = 0




X² - √3X - 2√3X + 6 = 0





X ( X - √3 ) - 2√3 ( X - √3 ) = 0





( X - √3 ) ( X - 2√3 ) = 0




( X - √3 ) = 0 OR ( X - 2√3 ) = 0





X = √3 OR X = 2√3.
Answered by abhi569
0
x² - 3√3x + 6 = 0

=> x² - ( 2√3 + √3 ) x + 6 = 0

=> x² - 2√3x - √3x + 6 = 0


=> x( x - 2√3 ) - √3( x - 2√3 ) = 0

=> ( x - √3 ) ( x - 2√3 ) = 0


 \mathbf{By \:  \:  Zero  \:  \: Product  \:  \: Rule } \\  \\ x = 2  \sqrt{3}  \:  \:  \:  \: or \:  \:  \:  \: x =   \sqrt{3}

Similar questions